Analysis of factors related to behaviours to prevent sexual assault of teenage girls - Pradanie, Retnayu; Yunitasari, Esti; Wibawati, Adinda Reza; Abigail, Wendy (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the factors associated with the behaviour of teenage girls in terms of preventing a sexual assault. Method: The descriptive, cross-sectional, correlational study was conducted in April 2021 at a senior high school in Cibitung, Bekasi, Indonesia, after approval from the ethics review committee of the Faculty of Nursing, Universitas Airlangga. The sample comprised class X-XII students aged 15- 19 years. Data was collected using a questionnaire. Data was analysed with logistic regression test using SPSS 20. Results: Of the 139 subjects, 52 (37.4%) were aged 16 years, 58 (41.7%) were in class XII. Significant relationship of behaviour to prevent sexual assault was found with knowledge (p=0.008), attitude (p=0.010) and peer interaction (p=0.007). Conclusion: Preventing sexual assault behaviour among girls was found to be related to knowledge, attitude and peer interaction. Keywords: Adolescent, Sex offenses, Violence, Knowledge, Attitudes, Practice.